Persepsi Peringatan Kesehatan Bergambar pada Bungkus Rokok di Kota Pontianak - Ridha, Abduh; Marlenywati, Marlenywati; Helwan, Urai (JUMANTIK (Jurnal Mahasiswa dan Peneliti Kesehatan), 2016)
The number of smokers in Indonesia were about 34.7%. More than 1/3 of population in West Kalimantan are smokers. The proportion increases when compared to the proportion of smokers in 2007, about 27.2% (MoH, 2011). One solution implemented by the government through Health Law2009 that the provisions of pictorial health warnings on cigarette packs. The purpose of this study to determine the relationship perception of pictorial health warnings with smoking status. The study designwas cross-sectional. The instruments used for data collection was a structured questionnaire. Sample size was 300 Pontianak Citizen. To see the relationship betweeen independent variables and dependent variable using Somer'd,chi-square test and logistic regretion. Results are: there are significant association among smoking status and opinion about the effectiveness of influence of PHW on the awarness smoking effect (P <0,05); there are significant association among smoking status and opinion about the effectiveness of PHW than written messages (P <0,05); there ware no relationship between smoking status and opinion about the most informative PHW (P value> 0.05). The warnthat showing the organ damage due to mouth, throat and lungs cancer had more impact than the other images. Warn picture should be a graphic imagery organ tobacco-related illness.Keyword: warn picture, opinion, smoking status